Photocatalytic degradation of indigo carmine by ZnO photocatalyst under visible light irradiation - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
In this work, the photocatalytic degradation of indigo carmine (IC) using zinc oxide suspension was studied. The effect of influential parameters such as initial indigo carmine concentration and catalyst loading were studied with the effect of Vis irradiation in the presence of reused ZnO was also investigated. The increased in initial dye concentration decreased the photodegradation and the increased catalyst loading increased the degradation percentage and the reused-ZnO exhibits lower photocatalytic activity than the ZnO catalyst. It has been found that the photocatalytic degradation of indigo carmine obeyed the pseudo-first-order kinetic reaction in presence of zinc oxide. This was found from plotting the relationship between ln (C0/Ct) and irradiation the rate constant of the process.UV- spectrophotometer was used to study the indigo carmine photodegradation.